2010
DOI: 10.1021/jp909697k
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon-Assisted Degradation of Toxic Pollutants with Ag−AgBr/Al2O3 under Visible-Light Irradiation

Abstract: AgBr coated with silver (Ag) nanoparticles (NPs) were highly dispersed on ordered mesoporous γ-Al 2 O 3 (MA) by the deposition-precipitation method with surfactant (Ag-AgBr/MAP). The catalyst showed high and stable photocatalytic activity for the degradation and mineralization of toxic persistent organic pollutants, as demonstrated with 2-chlorophenol (2-CP), 2,4-dichlorophenol, and trichlorophenol under visible light or simulated solar light irradiation. The dispersion of Ag-AgBr NPs on MA strongly affected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 187 publications
(90 citation statements)
references
References 25 publications
3
84
0
Order By: Relevance
“…In consequence, it can be concluded that HO· plays a key role in the photocatalytic degradation of EE2. This result is consistent with above mentioned photocatalytic mechanism of Ag/AgCl @ chiral TiO 2 nanofibers since all of h + and Cl 0 can undergo a series of reactions and produce HO· [23,24]:…”
Section: Photocatalytic Mechanism Of Ag/agcl @ Chiral Tio 2 Nanofiberssupporting
confidence: 90%
“…In consequence, it can be concluded that HO· plays a key role in the photocatalytic degradation of EE2. This result is consistent with above mentioned photocatalytic mechanism of Ag/AgCl @ chiral TiO 2 nanofibers since all of h + and Cl 0 can undergo a series of reactions and produce HO· [23,24]:…”
Section: Photocatalytic Mechanism Of Ag/agcl @ Chiral Tio 2 Nanofiberssupporting
confidence: 90%
“…Cu 2 O nanocubes were prepared as described previously, and stored in refrigerator before used [29]. Then, Cu 2 O was deposited onto Al 2 O 3 during the deposition-precipitation process of Ag-AgBr as reported in our previous work [27]. Briefly, 0.08 g of Cu 2 O and 0.6 g of ␥-Al 2 O 3 was added to 60 mL of distilled water, and the suspension was sonicated for 30 min.…”
Section: Preparation Of Catalystsmentioning
confidence: 99%
“…Therefore, the formation of bigger Ag 0 cluster leaded to the decrease of the photocatalyst activity because the surface plasmon resonance of Ag NPs depended on particle size [32][33][34]. In contrast, Ag-AgBr/Al 2 O 3 exhibited activity successive cycles without any treatment [27], indicating no formation of the bigger Ag 0 cluster in the process of photocatalysis. The results verified that the faster transfer of electron occurred between Ag + and Ag 0 on the surface of In order to illustrate the effect of Cu 2 O on the charge separation and charge-transfer processes, CV analyses were performed at the different photoanodes in a N 2 -saturated 0.1 M sodium sulfate aqueous solution under > 420 nm visible light irradiation (Fig.…”
Section: Photostability and Agmentioning
confidence: 99%
See 1 more Smart Citation
“…AgBr is an important semiconductor widely used as a photosensitive material in photography and as a photocatalyst for the degradation of pollutants or destruction of bacteria [24,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. Compared with BiOBr [18], AgBr [45] has a narrower band gap and higher visible-light absorption.…”
mentioning
confidence: 99%